Toxicity and biodistribution of alginate-stabilized AgNPs upon 14-days repeated dose oral administration in mice - Dian Pribadi Perkasa, Wawaimuli Arozal, Kusmardi Kusmardi, Mukh Syaifudin, Tri Purwanti, Roza Indra Laksmana, Afiq Azfar Pratama, Irawan Sugoro, Dien Puji Rahayu (Journal of Applied Pharmaceutical Science, 2024)
This study evaluated the effect of incremental doses of oral alginate-stabilized silver nanoparticles (AgNPs) on toxicity outcomes and biodistribution over 14 days. Twenty-five male ddY mice strain were randomly divided into five groups as follows: control, silver ion 5.0 mg/kg BW, and AgNPs 2.5, 5.0, and 10.0 mg/kg BW, respectively. There were no significant effects on body weight, organ index, hematology, or biochemical parameters in AgNP-treated mice at doses of up to 10 mg/kg BW. The silver content in tissue was undetectable, and no toxic effect was observed upon repeated oral administration at 2.5 mg/kg BW. However, histopathological analysis showed mild to severe colon and liver injuries in AgNPs groups at doses 5.0 mg/kg BW and higher. While, silver ion seems the most toxic form of silver which showed the highest silver deposition in all studied organs, an increase in Alt and lactate dehydrogenase levels, and perform severe pathological features in liver and colon tissues. These results suggest that the liver is the main target organ for toxicity of alginate-stabilized AgNPs. In the context of locally acting drugs, further bioactivity study on alginate-stabilized AgNPs is recommended at a dose lower than 2.5 mg/kg BW in which inconspicuous toxic effect is observed upon repeated oral administration.
Keywords: Silver nanoparticles, alginate, toxicity, biodistribution, systemic uptake